2008
DOI: 10.1016/j.tox.2007.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of S-adenosyl-l-methionine (SAMe) and N-acetylcysteine (NAC) protective effects on hepatic damage when administered after acetaminophen overdose

Abstract: In the clinical setting, antidotes are generally administered after the occurrence of a drug overdose. Therefore, the most pertinent evaluation of any new agent should model human exposure. This study tested whether acetaminophen (APAP) hepatotoxicity was reversed when S-adenosyl-L-methionine (SAMe) was administered after APAP exposure, similar to what occurs in clinical situations. Comparisons were made for potency between SAMe and N-acetylcysteine (NAC), the current treatment for APAP toxicity. Male C57BL/6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
38
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 37 publications
3
38
0
4
Order By: Relevance
“…Most treatment strategies are based on the same principles as NAC and work as a direct antidote through GSH repletion (9,10). Here, we established zebrafish as a physiologically relevant model of APAP hepatotoxicity, amenable to compound screening; using this platform, we identified PGE2 as a synergistic hepatoprotective agent in combination with NAC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most treatment strategies are based on the same principles as NAC and work as a direct antidote through GSH repletion (9,10). Here, we established zebrafish as a physiologically relevant model of APAP hepatotoxicity, amenable to compound screening; using this platform, we identified PGE2 as a synergistic hepatoprotective agent in combination with NAC.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical efficacy of NAC treatment was shown for patients presenting after APAP ingestion; however, no conclusive clinical trials were conducted to elucidate its efficacy and optimal treatment window. Therapeutic benefits have been shown in mammalian models for other antioxidants (9,10) that function to restore GSH levels. Compounds that support liver recovery from APAP injury rather than antagonizing the mechanism of toxicity are lacking.…”
mentioning
confidence: 99%
“…Asetaminofenin doku hasarına sebep olmasında lipid peroksidasyonunun yakından ilgisi olduğu ileri sürül-mektedir. Asetaminofen hepatotoksisitesinde literatür-deki çalışmalarda plazma [21,23] ve karaciğer dokusu [24][25][26] MDA düzeylerinin arttığı bildirilmiştir. Literatür ile uyumlu olan bulgularımız ışığında; asetaminofen kaynaklı toksik hepatitte MDA düzeyinin yüksek bulunmasının, serbest radikaller ile oluşan lipid peroksidasyonunun sonuçlarından biri olduğunu söyleyebiliriz.…”
Section: Discussionunclassified
“…Terneus ve ark. [26] lipid peroksidasyon ürünlerinden ve aynı zamanda bir aldehid olan 4-hidroksinonenal molekülünün parasetamol uygulanan gruplarda karaciğer dokusu proteinlerine bağlandığını bildirmişlerdir. Literatürdeki bilgiler ışığında çalışmamızda gördüğümüz karaciğer dokusu MDA düzeyinin yüksek olması; MDA'nın hem oluştuğu bölgede hem de uzak dokularda olumsuz etkilerini devam ettireceğini düşün-dürmektedir.…”
Section: Discussionunclassified
“…Recent experimental hepatotoxicity studies demonstrated increased MDA levels in plasma and liver tissue (39,40). The 4-hydroxynonenal molecule, which is a lipid peroxidation product and also an aldehyde, is reported by Terneus et al (41) to be linked to liver tissue proteins in acetaminophen-induced groups. Based on our fi ndings and those found in literature; we can claim that increased MDA levels in acetaminophen-induced toxic hepatitis is one of the consequences of lipid peroxidation caused by free radicals.…”
mentioning
confidence: 96%